STRUGGLE IN TERE LIYE’S NOVEL ABOUT YOU - Evi Oktaviani; Susi Ekalestari (Universitas Islam Sumatera Utara, 2023)
This study aims to reveal the protagonist’s struggle and describe how the protagonist struggles to survive in Tere Liye's novel About You. Maizler's theory was applied as the main theory and Ahmadi’s theory as the sub-theory. Therefore, the analysis of this study concerns the kinds of struggle: positive struggle, negative struggle, inevitable struggle, and chosen struggle. It also discusses the factors of struggle. They are will, sympathy, encouragement, and desire. The novel About You talks about the story of a woman named Sri Ningsih who faces many struggles in her life. This research adopts a qualitative design in which the data, the analysis, and the findings are presented in the form of a description. The result shows that three kinds of struggle are experienced by the protagonist. She carries out positive struggle, inevitable struggle, and chosen struggle. Furthermore, four factors of struggle are experienced by the protagonist. The factors are will, sympathy, encouragement, and desire.